Case report: a patient with pulmonary arterial hypertension transitioning from a PDE-5 inhibitor to Riociguat. Issue 1 (December 2016) - Poch, David
Abstract Background We present here the case of a patient with pulmonary arterial hypertension and NYHA Class II symptoms who transitioned from PDE-5i therapy to riociguat. No protocol currently exists for transitioning between these PAH medications. Case presentation A 59-year old male with a history of anorexigen use initially presented in 2008 and was felt to have non-operable small vessel disease. His care was transitioned to our center after insurance would not cover high-dose sildenafil in addition to ERA therapy. Conclusion This case demonstrates a safe and successful transition from higher dose PDE-5is to riociguat with no interruption in therapy.